Identification of biomarkers associated with immune scores in diabetic retinopathy - Zhang, Yi; Zhu, Weidong; Wang, Jianming; Zuo, Yi (Frontiers in Endocrinology, 2023)
Background: Diabetic retinopathy (DR) causes irreversible visual impairment in diabetes mellitus (DM) patients. Immunity played a crucial role in DR. Nevertheless, the triggering mechanism of DR was not yet thorough enough. Herein, we aim to identify the immune-associated genes as biomarkers associated with immune scores that can distinguish early DR from DM without DR.In this study, total RNA of peripheral blood mononuclear cells (PBMCs) samples from 15 non-proliferative DR patients and 15 DM patients without DR were collected and the transcriptome sequencing data were extracted. Firstly, the target genes were obtained by intersecting the differentially expressed genes (DEGs) which were screened by "limma" and the module genes (related to immune scores) which were screened by "WGCNA". In order to screen for the crucial genes, three machine learning algorithms were implemented, and receiver operating characteristic (ROC) curve was used to obtain the diagnostic genes. Moreover, the gene set enrichment analysis (GSEA) was performed to understand the function of diagnostic genes, and analysis of the proportions of immune cells and their association with diagnostic genes were performed to analyze the pathogenesis of DR. Furthermore, the regulatory network of TF-mRNA-miRNA was built to reveal the possible regulation of diagnostic genes. Finally, the quantitative real-time polymerase chain reaction (qRT-PCR) was performed to verify the mRNA level of diagnostic genes.Results: Totals of three immune-associated diagnostic genes, including FAM209B, POM121L1P and PTGES were obtained, and their expression was increased in PBMCs samples of DR, and qRT-PCR results confirmed these results. Moreover, the functions of these genes were associated with immune response. The expression of POM121L1P and PTGES was significantly negatively associated with naive B cell, and the expression of FAM209B was significantly negatively associated with immature dendritic cell. Besides, ESR1 could regulate both FAM209B and PTGES.This study identified three immune-associated diagnostic genes FAM209B, POM121L1P and PTGES as biomarkers associated with immune scores in DR for the first time. This finding might proffer a novel perspective of the triggering mechanism of DR, and help to understand the role of immune-associated genes in the molecular mechanism of DR more deeply.